Complete Denture Delivery Appointment for Oral Rehabilitation of Edentolous Patients: A Case Series - Pinharandas, Mariana Mangas (2022)
Trabalho Final do Mestrado Integrado em Medicina Dentária apresentado à Faculdade de Medicina